Foreign Direct Investment in Southeastern Europe : How (and How Much) Can Policies Help? - Ribakova, Elina (IMF Working Papers; Working Paper ;, 2005)
Gravity factors explain a large part of Foreign Direct Investment (FDI) inflows in Southeastern Europe-a region not comprehensively covered before in econometric studies-but hostcountry policies also matter. Key are policies that affect relative unit labor costs, the corporate tax burden, infrastructure, and the trade regime. This paper develops the concept of potential FDI for each country, and uses its deviation from actual levels to estimate what policies can realistically be expected to achieve in terms of additional FDI. It also finds evidence that above a certain threshold, the importance of some policies for attracting FDI is distinctly different.